Analyses of a Dipole Antenna Loaded by a Cylindrical Shell of Double Negative (DNG) Metamaterial - Khan M. Z. Shams; Mohammod Ali (International Journal of Antennas and Propagation)
The current distribution, input impedance, and radiation pattern of a cylindrical dipole antenna enclosed by a thin cylindrical shell of double negative (DNG) metamaterial are computed using the piecewise sinusoidal Galerkin formulation. In the presence of the DNG shell, the dipole antenna exhibits three interesting characteristics. The input impedance shows potentials for wide bandwidth due to the relative insensitivity of the impedance with frequency. Within specific ranges of DNG material parameter values, the dipole shows resonance at much lower frequencies than its resonant frequency in free space. The dipole does not show change in the direction of the principal beam nor does it show signs of beam splitting and side lobes even when the antenna length approaches one and a half wavelength.